Cumulative energy demand and global warming potential of a building-integrated solar thermal system with/without phase change material. (15th April 2018) - Lamnatou, Chr.; Motte, F.; Notton, G.; Chemisana, D.; Cristofari, C.
Abstract: Building-integrated solar thermal (BIST) systems are a specific type of solar thermal systems which are integrated into the building and they participate in building functionality. The present article is about the life-cycle assessment of different options of a BIST system (Mediterranean climatic conditions: Ajaccio, France). The environmental profile of the studied configurations is assessed by means of CED (cumulative energy demand), GWP (global warming potential) and EPBT (energy payback time). The proposed configurations (for the collector) include: i) a system without PCM (phase change material) using only rock wool as insulation and ii) a system with PCM (myristic acid) and rock wool. Concerning life-cycle results based on CED and GWP 100a (scenario without recycling), the configuration without PCM shows 0.67 MJprim /kWh and 0.06 kg CO2.eq /kWh while the configuration with PCM presents 0.74 MJprim /kWh and 0.08 kg CO2.eq /kWh. Regarding EPBT, if the inputs for pumping/auxiliary heating are not taken into account, both configurations (with/without PCM) have almost the same EPBT (about 1.3 years). On the other hand, if the inputs for pumping/auxiliary heating are considered, EPBT is lower for the system with PCM. In addition, scenarios with recycling have been examined and the results demonstrate that recycling considerably improves the environmental profile of the studied configurations. Highlights: Building-integrated solar thermal system with/without PCM (phase change material). Case A without PCM (LCA without recycling): 0.06 kg CO2.eq /kWh; 0.67 MJprim /kWh. Case B with PCM (LCA without recycling): 0.08 kg CO2.eq /kWh; 0.74 MJprim /kWh. Case B with PCM (LCA with recycling): 0.05 kg CO2.eq /kWh; 0.45 MJprim /kWh. Energy payback time without pumping/auxiliary heating: 1.3 years for both cases.